Textos factuais em material didático de português como língua de acolhimento: um estudo de gêneros de texto na perspectiva sistêmico-funcional - Gugelmim, Lorilei de Moraes (2021)
This research has as the general objective to analyse texts with the potential to instantiate the genres of the families of procedures, reports and explanations that are part of the factual texts, which general social purpose is to inform in specific didactic material for the teaching and learning of Portuguese as a Host Language (PLAc). To reach the proposed objective, theoretical bases of Systemic Functional Linguistics are used (HALLIDAY, 1989, 1994; HALLIDAY; MATTHIESSEN, 2004, 2014), focusing on the approach of genre of Sydney School (MARTIN; ROSE, 2008; DEREWIANKA, 2009; CHRISTIE; DEREWIANKA, 2010; ROSE; MARTIN, 2012; EMILIA; CHRISTIE, 2013). Regarding the methodological approach, this research is characterized as qualitative. As a universe of analysis, the didactic material Pode Entrar – Português do Brasil para Refugiadas e Refugiados (FEITOSA et al., 2015) was selected, which is available for free download. Fifteen texts of this material are part of the research corpus, which have potential to instantiate genres of the families in study. The analytical procedures adopted are: description of the variables of register field, tenor and mode of each text selected; description and analysis of the linguistic occurrences of functions of the transitivity system, of the speech functions and the modality system; identification of the Schematic Structure of Genre (EEG) and confirmation of the socio-communicative purpose and, consequently, of the genres instantiated in the analysed texts. As result of the linguistic analyses, two instantiations of the genre protocol of the family of procedures were identified: nine instantiations of the genre descriptive report and two instantiations of the genre classification report of the family of reports, and no instantiation of genres of the family of explanations. These results evidence that language, in the analysed corpus, is being used mainly to describe and classify the information that is passed on to immigrants and refugees through Descriptive Reports and Classificatory Reports and, on a much smaller scale, to guide them on how to act through protocols. Two instances of unanticipated instantiations were identified at the beginning of the study: an instantiation of Historical Report, of the family of stories, and an instantiation of Exposition from a point of view, of the family of arguments. It is noteworthy that linguistic knowledge about the analysed genres can contribute to the social integration of immigrants and refugees, constituting itself as an inclusive linguistic policy, since it facilitates access to the social practices present in the daily lives of this public.